Ammonium transporters cooperatively regulate rice crown root formation responding to ammonium nitrogen. (17th February 2022) - Luo, Long; Zhu, Ming; Jia, Letian; Xie, Yuanming; Wang, Ziniu; Xuan, Wei
Abstract: Crown roots (CRs) are major components of the rice root system. They form at the basal node of the shoot, and their development is greatly influenced by environmental factors. Ammonium nitrogen is known to impact plant root development through ammonium transporters (AMTs), but it remains unclear whether ammonium and AMTs play roles in rice CR formation. In this study, we revealed a significant role of ammonium, rather than nitrate, in regulating rice CR development. High ammonium supply increases CR formation but inhibits CR elongation. Genetic evidence showed that ammonium regulation of CR development relies on ammonium uptake mediated jointly by ammonium transporters OsAMT1;1, OsAMT1;2; OsAMT1;3, and OsAMT2;1, but not on root acidification which was the result of ammonium uptake. OsAMTs are also needed for glutamine-induced CR formation. Furthermore, we showed that polar auxin transport dependent on the PIN auxin efflux carriers acts downstream of ammonium uptake and assimilation to activate local auxin signaling at CR primordia, in turn promoting CR formation. Taken together, our results highlight a critical role for OsAMTs in cooperatively regulating CR formation through regulating auxin transport under nitrogen-rich conditions. Abstract : Ammonium-induced rice crown root formation relies on the joint action of OsAMT ammonium transporters on ammonium uptake and glutamine biosynthesis, and is mediated by OsPIN auxin transport.